2022
DOI: 10.1115/1.4053615
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Axial Distance and Duct Angle in the Improvement of Power Generation in Duct Augmented Wind Turbines

Abstract: Diffuser augmented wind turbines (DAWTs) are incredibly beneficial to low wind speed areas. The duct that surrounds the turbine improves the power output by accelerating the approaching wind directing the wind through the blade. The power output of DAWT mainly depends on the duct length by turbine diameter (L/D) ratio, duct angle, axial distance, and tip clearance between the blade and duct. This article gives an insight into the performance variation of DAWT for various duct L/D ratios. Numerical simulations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…In the present study, six geometrical parameters were identified from the literature: diffuser angle (𝜃 ), concentrator angle (𝜃 ), concentrator length (𝐿 ), diffuser length (𝐿 ), Research studies have indicated that these parameters affect the velocity augmentation of the diffuser-augmented wind turbine (DaugWT), the concentrator-augmented wind turbine (CaugWT), and the CDaugWT [26,29,55,56]. However, most of these studies focused on analysing each parameter's influence independently, while other parameters were held constant [42,57,58]. The present study investigated the interaction between these parameters and their contribution towards velocity augmentation.…”
Section: Surface Response Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, six geometrical parameters were identified from the literature: diffuser angle (𝜃 ), concentrator angle (𝜃 ), concentrator length (𝐿 ), diffuser length (𝐿 ), Research studies have indicated that these parameters affect the velocity augmentation of the diffuser-augmented wind turbine (DaugWT), the concentrator-augmented wind turbine (CaugWT), and the CDaugWT [26,29,55,56]. However, most of these studies focused on analysing each parameter's influence independently, while other parameters were held constant [42,57,58]. The present study investigated the interaction between these parameters and their contribution towards velocity augmentation.…”
Section: Surface Response Methodologymentioning
confidence: 99%
“…Notably, it is suitable for adverse pressure gradients, insensitive to free-stream turbulence in the far wake region, and eliminates the need for damping functions [72]. The model choice was based on extensive literature recommendations for aerodynamic purposes, especially in shrouded wind turbines [9,11,12,37,40,42,[67][68][69][72][73][74][75][76][77][78].…”
Section: Turbulence Model Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying CFD techniques to analyze the aerodynamics of wind turbines enables a deeper understanding of fluid dynamics within the wind field, thus enabling precise predictions of turbine performance [40,41]. Such a statement is evident from the review of the above papers, and it can be found that most of the above studies were conducted using computational fluid dynamics (CFD), such as Abe and Ohya [19], Abe et al [20], Jafari and Kosasih [22], Roshan et al [23], El-Zahaby et al [24], Heikal et al [27], Klistafani and Mukhsen [28], Anbarsooz et al [29], Arifin et al [30], Ramayee and Supradeepan [32], Hashem et al [33], Jauhar et al [34], Mutasher et al [35], Hashem et al [38], Avallone et al [39], etc. ; and the review paper by Agha et al [42] also emphasized that CFD plays a vital role in the design and performance improvements of the DAWT.…”
Section: Introductionmentioning
confidence: 93%
“…The influences of rotor axial position, diffuser length, and opening angle on the power generation of DAWTs were numerically studied by Ramayee and Supradeepan [32]. Their parametric studies showed that the optimal diffuser opening angle is a function of its length, so it should not be fixed and has to be kept as a variable when changing the diffuser length.…”
Section: Introductionmentioning
confidence: 99%